Influence of reactive sheet resistance on radiation characteristics and dipoles and loop aerials dispersion - Gerasimovich, G. V.; Jubko, A. P. (Видавництво Національного університету "Львівська політехніка", 2009)
For the construction of the wire aerials with reduced sizes (the spiral aerials, the dipoles) the thin conductors possessing reactive sheet resistance are used. However influence this resistance on the range of properties and dispersion characteristics are studied insufficiently, there are also no information about loop aerials made of impedance materials in the literature. There are the results of the numerical modeling of the Yagi and loop aerials with reactive sheet resistance in the report. The reactive resistance is realized by turning of a thin conductor into the spiral of radius ao   (  -wave length).
Keywords: тhin conductors; reactive sheet resistance conductors; wire aerials; integra equation method